Improvement in the Blood Urea Nitrogen and Serum Creatinine Using New Cultivation of Cordyceps militaris. (23rd March 2022) - Yang, Chih-Hui; Kuo, Wen-Shuo; Wang, Jun-Sheng; Hsiang, Yi-Ping; Lin, Yu-Mei; Wang, Yi-Ting; Tsai, Fan-Hsuan; Lee, Chun-Ting; Chou, Jiun-Hua; Chang, Huei-Ya; Wang, Lung-Shuo; Wang, Shu-Chi; et al.
Abstract : Background . Chronic kidney disease (CKD) is a critical public health issue with a huge financial burden for both patients and society worldwide. Unfortunately, there are currently no efficacious therapies to prevent or delay the progression of end-stage renal disease (ESRD). Traditional Chinese medicine practices have shown that Cordyceps militaris ( C. militaris ) mycelia have a variety of pharmacologically useful properties, including antitumor, immunomodulation, and hepatoprotection. However, the effect of mycelial C. militaris on CKD remains unclear. Methods . Here, we investigated the effects of C. militaris mycelia on mice with CKD using four types of media: HKS, HKS with vitamin A (HKS + A), CM, and CM with vitamin A (CM + A). Results . The results at day 10 revealed that the levels of blood urea nitrogen (BUN) were significantly lower in the HKS (41%), HKS + A (41%), and CM + A (34%) groups compared with those in the corresponding control groups (nephrectomic mice). The level of serum creatinine in the HKS + A group decreased by 35% at day 10, whereas the levels in the HKS and CM + A groups decreased only by 14% and 13%, respectively, on day 30. Taken together, this is the first report using four new media (HKS, HKS + A, CM, and CM + A medium) for C. militaris mycelia. Each medium of mycelial C. militaris on CKD exhibits specific effect on BUN, serum creatinine, body weight, total protein, and uric acid. Conclusions . Taken together, this is the first report using four new media (HKS, HKS + A, CM, and CM + A medium) for C. militaris mycelia. Each medium of mycelial C. militaris on CKD exhibits specific effects on BUN, serum creatinine, body weight, total protein, and uric acid. We concluded that treatment with C. militaris mycelia cultured in HKS or CM + A medium could potentially prevent the deterioration of kidney function in mice with CKD.